THE TIDAL OSCILLATIONS UNDER THE SEA LEVEL RISE EFFECTS IN CENTRAL VIETNAM - Trinh, Nguyen Quoc; Huan, Nguyen Minh; Tien, Pham Van; Vinh, Nguyen Quang (Vietnam Journal of Marine Science and Technology, 2015)
The tide is one of the most important phenomena in the ocean. In the world as well as in Vietnam, the tide was studied very early and great achievements have been recorded. However, under the impact of climate change and sea level rise, the local - to - regional - scale changes will cause significant changes in the coastal system. This paper gives some results of research on the tidal changes in the central region of Vietnam by using the hydrodynamic model and data analysing model. The simulation results of the tide in the central coast of Vietnam show that the tide can change both in the amplitude and phase distribution of the tidal constituents as M2, S2, K1 and O1. Specifically, the results of the average values of M2 are 0.1 m and 10.20; for S2 are 0.12 m and 12.50; for K1 are 0.2 m and 17.20; for O1 are 0.21 m and 20.20. Some results of this study showed that the most important contribution to the change of the tide in the region is the change of topography and the submerged areas.